GENEROSITY BEHAVIOR IN THE MILLENNIAL GENERATION OF PHILANTHROPS - Tengku Nuranasmita; Khairil Fauzan K (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Several things or factors that become or influence itIncome level greatly influences a person's motivation to behave generously. The tendency of people to spend their income to fulfill their personal satisfaction. Although there are also some people who spend their wealth for the benefit of other people or humanitarian interests, namely by giving charity. Another phenomenon that can encourage someone's generosity is when the law of diminishing marginal utility applies, where the assets someone owns can no longer provide satisfaction, so they are encouraged to donate them to other people.This research aims to determine the description of generosity behavior in the philanthropic millennial generation. The design of this research is phenomenological. The number of respondents in this study was three people with three informants as sources of triangulation. The technique for collecting respondent data uses purposive sampling. Research data was collected through observation and interviews. Data analysis techniques are carried out by means of data reduction, data display, and verification. The research results show that respondents can feel generosity behavior. For the behavioral aspect of generosity, the three respondents also felt life satisfaction, because more positive affection appeared. Internal factors are also very influential, so that respondents have quite high levels of generosity behavior where the three respondents have strong personalities in enjoying life and are happy when making other people happy (social spirit), have the principle of feeling what other people feel, and have strong faith. towards God Almighty. Support from family, co-workers and social support which are external factors also greatly influence the high level of generosity behavior in the three respondents.